Ultrapartikel tulang ikan kaya kalsium untuk peningkatan gel surimi pada pemanasan gelombang mikro: Calcium-rich fish bone ultraparticles for enhancing surimi gel strength under microwave heating - Riyanto, Bambang; Ramadhan, Wahyu; Trilaksani, Wini; Isnaini, Cahyuning; Wulandari, Ayu Septi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Achieving optimal gel strength is critical for ensuring the desired texture in surimi-based products. This study aims to determine the best concentration of calcium-rich fish bone ultraparticles (UpTIK) in surimi of threadfin bream fish based on the gel strength of surimi and endogenous TGase activity upon microwave heating. UpTIK was produced through calcination and nano-milling, resulting in a high calcium content. Microwave heating was applied with varying concentrations of UpTIK (0; 0.5; 1; and 2%). The parameters analyzed included the activity of endogenous TGase enzyme extract, L*a*b* color analysis and whiteness, water holding capacity (WHC), salt-soluble protein (PLG), and gel strength. The results indicated that a 1% UpTIK concentration achieved the highest TGase activity (0.47±0.05 U/mL) and gel strength (647.17 g/cm²). Additionally, the inclusion of UpTIK improved water holding capacity and salt-soluble protein content while preserving the whiteness of the surimi. Microwave heating also significantly reduced processing time by up to threefold compared to conventional heating. This study demonstrated a novel approach for activating endogenous TGase using UpTIK under microwave heating, providing a promising strategy for diversifying surimi products derived from tropical fisheries.